STRATEGI PENINGKATAN KINERJA KARYAWAN: ANALISIS SWOT - Iryani Iryani; Deasy Deasy (Cross-border, 2021)
This study aims to formulate strategies that must be applied for performance development by analyzing the company's strengths, weaknesses, opportunities, and threats through analysis at PT. Oremus Bahari Mandiri Surabaya based on SWOT analysis. The type of data used in this study is quantitative data, while the source of research data is primary data. The number of samples used as many as 35 people with the census technique. Based on the results of the SWOT analysis the position of PT. Oremus Bahari Mandiri is in quadrant I, meaning that PT. Oremus Bahari Mandiri has internal strength that can be relied on to take advantage of opportunities that are open in an effort to develop performance. The strategy that must be applied in this condition is to support an aggressive growth policy.